Implementasi Model Belajar Project Based Learning Guna Meningkatkan Keterampilan Belajar Pada Anak Usia Dini - fitriani, rohyana (Jurnal Golden Age, 2024)
This study aims to see and examine the effectiveness of the Project Based Learning model in improving learning skills in early childhood in the 5 to 6 year age group at Al-Ma'arif Mujur Kindergarten. Through specially designed projects with a series of prepared projects, children are invited to actively explore, collaborate, and solve problems and children are given the opportunity to express their ideas. The research method used this time is a descriptive qualitative research method with the research subject being early childhood age group 5 - 6 years. Data collection techniques used in this study are observation, documentation and interview techniques. The results of this study showed a significant increase in almost all aspects of children's learning skills involved in Project Based Learning projects. The conclusion is that the project based learning model can improve early childhood learning skills, especially the 5 to 6 age group.